“The Art of Writing” as a Value in the 1788 Dissertation by Jacek Idzi Przybylski, Librarian of the Royal Main School in Krakow - Kuryan, Inesa (Slavistica Vilnensis, 2025)
We rarely consider whether the alphabet holds value for us. It is more of a tool for everyday writing, which value is variable and has its own history. The most precious aspect is that the act of writing with letters inherently contains the condition of commemorating only important content for future generations. An inspiring text from 1788 on the development of the Art of Writing among the Ancients by Jacek Idzi Przybylski (1756–1819), a well-known Polish figure of the Enlightenment, translator, and university librarian in Kraków, allows us to view texts and accumulated knowledge, for which universities ultimately bore responsibility, from both diachronic and axiological perspectives. This is crucial for understanding the university as a foundation for future generations of students, scholars, creators, and, more broadly, citizens.The author speaks about texts through the example of classical philology and its ethical values, reflecting on how writing and texts developed with an emphasis on particular skills in thinking and expressing emotions. For a long time, these skills were singled out as the only ones worthy of being recorded, commemorated, and passed on to future generations in the development of human civilization. The earliest attempts to record events using alphabetic writing were, for centuries, linked to valuable messages, maturing into outstanding content in both painting and literature. The axiology of the earliest ancient texts – based on high poetic standards – shaped the translation work of Jacek Idzi Przybylski,, a somewhat forgotten scholar and translator of the late 18th and early 19th centuries. He, in turn, enabled students at the University of Vilna in the early 19th century to develop their own talents through his works and, as a result, demonstrate true “art of writing” in the form of outstanding works of Vilnian Romanticism.
Keywords: alphabetic writing as a brilliant invention; development of the art of writing; ways of expressing thoughts and “stirring passions”; epic motifs in Vilnian Romanticism; Jacek Idzi Przybylski